Considering Ubuntu for satirical (online) communication: comments on Jesus is a Shangaan - Chasi, Colin; Lowane, Ntsako (Department of Communication Science, University of the Free State, 2016)
Satire is a genre of communication that enables people to say the unspeakable, often enabling powerful norms and powerful people to be questioned and challenged. As such, satire is a powerful weapon with which society may strike at and against oppression and other problematic orders. However, satire may also be misused to misrepresent and demean others. Meanwhile, in online encounters where people are not subject to a wide gamut of social controls and moral obligations are weakened by anonymity, people are liable to use satire in ways that are experienced by others as offensive and hurtful. This is arguably pointedly problematic in contexts where historical developments have marginalised and tribally positioned people to be the butt of jokes. This article examines these and related concerns in the light of the animated video Jesus is a Shangaan to argue that it is worthwhile to present a scholarly account of what the African moral philosophy of Ubuntu may say about how people should satirise. The conclusion is that there is a need for scholars to elaborate more systematically and adequately what Ubuntu requires of satirical communication – how African excellence can be understood when communication is satirical.
Keywords: Ubuntu; Satire; African communication; Shangaan; Online communication